Determinants of out-of-pocket health care expenditure in Peru, the Covid 19 pandemic and health insurances - García, Luis (2023)
This study quantitatively assesses the main determinants of out-of-pocket health expenditure as ability to pay (OOPE) in the period 2016-2020, including access to health insurance and getting sick from Covid 19 disease. Previous studies such as Petrera and Jimenez (2018) have only focused on Seguro Integral de Salud (SIS), but have not considered Essalud insurance. Insurance is expected to reduce OOPE while suffering from Covid 19 increases this expenditure. Using a fixed-effect panel data Tobit model, we find that SIS reduces OOPE for the poorest, while Essalud does so for the non-poor. On the other hand, Covid 19 strongly increases OOPE for poor and non-poor.